The Production Process and Aesthetics of Batik Motifs at Wardah Batik Industry House in Banjarnegara Regency - Imam Fauzi Ath Thaariq; Syafii, Syafii (Eduarts: Jurnal Pendidikan Seni, 2025)
Nowadays, the process of producing batik motifs has become an important subject of study due to the declining aesthetic value found in each piece created. Aesthetic value plays a role as a mediator in conveying the moral message inherent in each work. It also has a vital role as the spirit offered in each piece, making it crucial to preserve its existence. This study aims to describe the production process and understand the aesthetics of batik motifs at the Wardah Batik Industry House. The research uses a qualitative approach with data collection techniques such as observation, interviews, and document studies. The study found that the batik production process at the Wardah Batik Industry House includes the stages of creating batik designs, with ideas sourced from the local potential of Banjarnegara, which are explored and sketched into batik designs, followed by the production stages: transferring designs, batiking, dyeing, stripping, and soaking in softener. The aesthetics of the batik motifs at the Wardah Batik Industry House, from a Javanese aesthetic perspective, include: First, the cultural cosmological value, the order of the universe manifested in the depiction and repetition of motifs such as Batik Daun Kelapa (Coconut Leaf Batik), Batik Dawet Ayu (Ayu Dawet Batik), Batik Wajan Canting (Canting Wajan Batik), Batik Ikan (Fish Batik), and Batik Parang Mrica (Parang Mrica Batik), which are depicted symmetrically, balanced, and orderly, with repetition in both vertical and horizontal alignment. Second, symbolic classification, empan papan in the use of batik fabric for clothing, sarongs, and the depiction of motifs that apply the two-pattern categories like top-bottom and left-right. Third, the orientation of life values, harmony, religiosity, justice, mutual cooperation, family, egalitarianism, and respect, which are embodied in the distinctive batik motifs of the Wardah Batik Industry House.